Investigating dental variation in Perameles nasuta Geoffroy, 1804, with morphological evidence to raise P. nasuta pallescens Thomas, 1923 to species rank - Travouillon, Kenny J. (Zootaxa, 2016)
The long-nosed bandicoot, Perameles nasuta Geoffroy, 1804, found on the east coast of Australia, has two subspecies, P. n. nasuta Geoffroy, 1804 and P. n. pallescens Thomas, 1923. Until recently, this distinction has remained untested by either morphological or molecular studies. Based on a recently published but limited molecular study, two publications have recommended that P. pallescens be treated as a species distinct from P. nasuta. Here, the morphological distinction between P. pallescens and P. nasuta is tested by examination of museum specimens from throughout the combined species range, using both qualitative and quantitative techniques. No external features and very few cranial features were found to separate the two subspecies. However, dental morphology and measurements are effective at distinguishing two geographically distinct populations; while a complex pattern of clinal vs non-clinal trends in cranial size suggest a genetic disjunction that corresponds with the dentally-defined geographic groups. These findings support the raising of P. pallescens to species level. In terms of dental features, P. pallescens was found to be most similar to the fossil P. sobbei. The morphological phylogeny recovered P. pallescens as sister to P. nasuta, when no fossil Perameles taxa were included, probably as a result of little cranial differentiation between them. When fossil Perameles were included, the relationships between species of Perameles were unresolved, probably as a result of P. sobbei lacking cranial remains.